Unusual cause of filling defect in pulmonary artery: pulmonary artery sarcoma - Cisel Yazgan; Hakan Ertürk; Aysenaz Taskin (Pan African Medical Journal, 2020)
Pulmonary artery (PA) sarcoma is an extremely rare malignant tumor of pulmonary artery. It is often misdiagnosed as pulmonary thromboembolism (PTE) because of its clinical and imaging features which are quite similar to PTE. Multimodality diagnostic imaging and recognition of specific imaging characteristics with appropriate clinical suspicion are required to make correct diagnosis. In this report, we present a case of PA sarcoma with imaging and clinical features as well as emphasize significance of using multimodality imaging.
Keywords: Computed Tomography Angiography; R; Case Report; Sarcoma; Middle Aged; Pulmonary Artery; intimal sarcoma; Vascular Neoplasms; Diagnosis, Differential; Pulmonary artery; intimal sarcoma; pulmonary thromboembolism; pulmonary artery; Medicine; Humans; pulmonary thromboembolism; Female; Diagnostic Errors; Pulmonary Embolism; 3. Good health